Dimerization is necessary for MIM-mediated membrane deformation and endocytosis - Cao, Meng (2012)
Missing in metastasis (MIM also MTSS1) is an intracellular protein that binds to actin and cortactin and has an intrinsic capacity to sense and facilitate the formation of protruded membranous curvatures implicated in cellular polarization, mobilization and endocytosis. The N-terminal 250 amino acids of MIM undergo homo-dimerization and form a structural module with the characteristic of I-BAR domain. To discern the role of the dimeric configuration in the function of MIM, we designed several peptides able to interfere with MIM dimerization in a manner depending upon their lengths. Overexpression of one of the peptides abolished effectively MIM-mediated membrane protrusions and transferrin uptake. However, a peptide with a high potency inhibiting MIM dimerization failed to impact on its binding to actin and cortactin. Thus, our data indicates that the dimeric configuration is essential for MIM-mediated membrane remodeling and serves as a proper target to develop antagonists specifically against an I-BAR domain-containing protein.